THE ROLE OF THE ENGLISH LANGUAGE IN THE LIFE OF AN INTERNATIONAL STUDENT ABROAD AND ICELAND - Sindy Sulley 1996- (2024)
The review aims to examine the use of English as a primary medium of instruction for international students studying in Iceland. The literature review focuses on what can be considered academic achievements, psychological well-being and cultural integration at the tertiary level. Furthermore, the literature review aims to extend the existing literature by firstly identifying the challenges and opportunities of studying in an internationalized higher education context where English is the language of instruction and secondly addressing the existing gap in the literature with the disadvantages students who are compelled to study in English as a foreign language while identifying the socio-cultural implications associated with teaching and learning in English. This review is based on a qualitative data analysis of secondary data with a thematic foundation on language aptitude, emotional matters, and the integration of culture. The findings suggest that fluent English is positively affiliated with academic success: students with high fluency were faithfully engaged in their class work and coped better in an academic and social milieu. Anxiety about not being able to communicate with peers and the fear of negative judgments translated into emotional hardships in ministry. Inadequate verbalization led to anxiousness, which in turn led to self-doubts. These students had support from their peers as a coping strategy. The study may improve our understanding of salient but complex ways English is used in developing education outside English-speaking countries, notably in Iceland, and it echoes the need for sound teaching pedagogy and mental health resources. Hopefully, future research may map the effects of English language use on career and life mobility over a lifespan.